Mental Cognition in Descartes‘ Philosophy - كعيكاتي, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the relation of the mind in producing knowledge with both truth and Cartesian doubt . In this research, we talked in details about the position of the mind in Descartes‘ philosophy in general, and it’s association with thought processes, mainly Cartesian doubt which is based on examining the cognitive phenomena and refusing what the senses produce, which means that Descartes had rejected the sensory knowledge for the sake of mental knowledge, as the results that the mind approaches are real and could make the thought far from doubt and close to ultimate mental truths.